Project management in the tourism industry : the basics of TMBOK - Burukina, Olga A. (Nauka, 2019)
Purpose: the article aims at substantiating the applicability of project management methodology and tools to the tactical and strategic development of the tourism industry at both the global and national levels of economic development. The author sees the possibility of sustainable development of the tourism industry on the basis of a systems approach to improving the functioning of tourism enterprises using the tools and methods of project management. Taking into account the current contribution of tourism to the global economy and the national economies of many countries, the problem of sustainability of tourism enterprises and national tourism industries in general seems to be one of the foundations for solving the problems of sustainable development included in the 2030 Agenda for Sustainable Development. Methods: the study was conducted on the basis of a systematic approach with the use of logical and comparative analysis of various types of project management methodology potentially applied to tourism projects both for solving operational tourism problems and for the strategic development of tourism industries, as well as the method of structural-functional modeling aimed at laying the foundation for the tourism project management methodology. Results: the problem of sustainability of the tourism industry – the leading sector of the national economies of many countries and the global economy as a whole – has been considered using a systematic approach. An attempt was made to prove the applicability of the project management methodology and tools to the tourism industry and the dependence of the sustainable development of the tourism industry, both at the local and national levels, on more effective management of processes, programs and portfolios based on a systems approach and project management as a method to improve tourism firms’ operations. The methodology of project management in tourism as a driving force for social, economic and cultural change is considered as the basis for successful implementation of projects to ensure benefits for all stakeholders: tour operators, consumers of tourism projects, local communities and all companies involved in tourism projects. Conclusions and Relevance: currently, the tourism industry faces a situation in which tourism projects are implemented in the context of reactive risk and change management with the almost complete absence of proactive change management, which adversely affects the quality of tourism projects and greatly hinders the development of national tourism industries in general. The proposed concept of applying the project methodology based on the author’s model of project management in tourism, the model of the tourism project and the model of TMBOK (tourism management body of knowledge) provides for a system of measures necessary for integrating the project management methodology into the practice of tour operators for the further sustainable development of all tourism business stakeholders.
Keywords: tourism industry; project management; event management; domain specificity; PM model for tourism industry; tourism; sustainable development; tourism sector; projects; leadership (activity); Finland; tourist services; well-being; marketing; project managers; fi=Johtaminen ja organisaatiot|en=Management and Organization|